Cortical Thickness and Depressive Symptoms in Cognitively Normal Individuals: The Mayo Clinic Study of Aging - Pink, Anna; Przybelski, Scott A; Krell-Roesch, Janina; Stokin, Gorazd B; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Geda, Yonas E (Journal of Alzheimer's disease, 2017)
Altered cortical thickness has been observed in aging and various neurodegenerative disorders. Furthermore, reduced hippocampal volume has been reported in late-life depression. Even mild depressive symptoms are common in the elderly. However, little is known about the structural MRI measures of depressive symptoms in normal cognitive aging. Thus we sought to examine the association between depressive symptoms with cortical thickness and hippocampal volume as measured by brain MRI among community-dwelling participants. We conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging, involving cognitively normal participants (N = 1,507) aged≥70 years. We observed that depressive symptoms were associated with lower global cortical thickness and lower thickness in specific prefrontal and temporal cortical regions, labeled by FreeSurfer software, version 5.3. As expected, the strength of correlation was very small, given that participants were community-dwelling with only mild depressive symptoms. We did not observe associations between hippocampal volume and depressive symptoms. These findings may provide insight into the structural correlates of mild depressive symptoms in elderly participants.
Keywords: Hippocampus; Male; stárnutí; Psychiatric Status Rating Scales; senioři nad 80 let; Aged, 80 and over; depression; Humans; senioři; mužské pohlaví; Female; magnetická rezonanční tomografie; průřezové studie; Aging; Aged; deprese; Cross-Sectional Studies; ženské pohlaví; kognice; Magnetic Resonance Imaging; cortical thickness; magnetic resonance imaging; depressive symptoms; Cerebral Cortex; Neuropsychological Tests; Depression; hipokampus; neuropsychologické testy; lidé; Cognition; psychiatrické posuzovací škály; mozková kůra